SOME ACTION ON REFLECTION - Khan, Junaid Sarfraz (Journal of Ayub Medical College Abbottabad, 2011)
The healthcare professional in our age needs to PERFORM in complex and challenging healthcare environments. The importance of reflection, reflective practice and teaching and training to develop a reflective practitioner is frequently established in the literature. In fact, recent research on pedagogy stresses the importance of establishing a link between reflective learning and reflective practice as a means to developing adult learning and life long learning skills. Reflection and its three categories of reflection-in-action, reflection-on-action and reflection-on-the-future have been established as the panacea of all things wrong in the health education and health care delivery systems. Activities, therefore, to promote reflection are now being incorporated into undergraduate, postgraduate, and continuing medical education, and across a variety of health professions. Many definitions of reflection can be found. Dewey1 defined reflection as '˜active, persistent and careful consideration of any belief or supposed form of knowledge in the light of the grounds that support it and the further conclusion to which it ends'. This definition shares our understanding of critical thinking. Brockbank and McGill2 identify reflection as a '˜process or means by which an experience, in the form of thought, feeling or action, is brought into consideration, while it is happening or subsequently'. Secondly, and deriving from the first, '˜the creation of meaning and conceptualisation from experience and the potentiality to look at things as other than they are'. Action can specifically occur before reflection and thus something that requires reflexive '˜action' and '˜practice', can occur during reflection (and here on the continuum of action can change or remain unchanged as a result of reflection-in-action) or can be the consequence of reflection-afterprevious-action. The argument related to the balance between action and reflection is not a simple one. How much reflection follows as a result of action and vice versa is largely context, action, and '˜reflector' dependent. This context, action, reflection, relationship is presented in Table-1. The Upper Right square is the square that represents maximum action with maximum reflection. Again the balance between action and reflection is very situation, subject, experience, context, person and position dependent. Table-1: Context, Action, Reflection, Relationship (CARR) Reflection No Action Reflection Action No Reflection No Action No Reflection Action Reflection, strangely enough, is an in-built reflex mechanism. At least it should be thought of in this way and not as something inhuman and mechanical. There would not be such a person who does not value the part reflection plays in improving professional practice. SchÃ¶n introduced the concept of a reflective practitioner. SchÃ¶n states that professional knowledge is limited because it does not take into account the realities of professional life and practice.3,4 In this time and age, professional knowledge gained by students before entering the profession itself, is made to be as realistic to professional practice as possible. Knowledge before practice does not give the learner the true taste in entirety of the actuality in principle, nevertheless, newer learning techniques and practices like problem based learning, task based learning, community oriented education, work place education give a lot in terms of reality to education before practice. Furthermore, even practice, brings new challenges everyday, which require, intuition, assertion, initiative, reflection and notably action. The addition of the word '˜critically' to '˜reflective practice' brings a new dimension to the force of nature that is reflection. It allows the person involved in critical reflective practice, to critically analyse experiences, events, occurrences and knowledge based on the context, situation, relevance, existing knowledge, and attitude (affect) in order to improve his own understanding, action, and attitude towards his practice. Reflective practice is the foundation that supports healthcare delivery systems anywhere in the world. It is through critical reflective practice that we improve our clinical practice, patient encounters and health care delivery. Developing reflective practice is an important component of the training and education of the healthcare professionals and it should form both part of the taught as well as the hidden medical curriculum in Pakistan's universities.